2019
DOI: 10.1093/cid/ciz223
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Therapy for Pseudomonas aeruginosa Bloodstream Infections: How Long Is Long Enough?

Abstract: In a multicenter, observational, propensity-score–weighted cohort of 249 adults with uncomplicated Pseudomonas aeruginosa bacteremia, patients receiving short-course (median, 9 days; interquartile range [IQR], 8–10) therapy had a similar odds of recurrent infection or death within 30 days as those receiving longer courses (median, 16 days; IQR, 14–17).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 13 publications
2
59
2
Order By: Relevance
“…According to the inclusion and exclusion criteria, we excluded 112 studies by evaluating the titles and abstracts. After reading the full texts of the remaining eleven studies, only six studies containing a total of 2689 patients were included in the systematic review and meta‐analysis 12,13,20‐23 . Two studies were excluded due to the unavailability of data 11,24 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the inclusion and exclusion criteria, we excluded 112 studies by evaluating the titles and abstracts. After reading the full texts of the remaining eleven studies, only six studies containing a total of 2689 patients were included in the systematic review and meta‐analysis 12,13,20‐23 . Two studies were excluded due to the unavailability of data 11,24 .…”
Section: Resultsmentioning
confidence: 99%
“…The main causative pathogen was Escherichia coli , and the main source of bacteremia was the urinary tract. Five studies involved adults, 12,13,21‐23 while one involved children 20 . Four studies included patients diagnosed with uncomplicated gram‐negative bacteremia, 12,13,20,23 whereas two studies only included patients with Enterobacteriaceae bacteremia 21 or Pseudomonas aeruginosa in the bloodstream 22 …”
Section: Resultsmentioning
confidence: 99%
“…41 Recent data have suggested that 7 to 10 days of therapy are appropriate for the treatment of uncomplicated GNB bacteremia with early source control, including those caused by PSA. [103][104][105][106][107][108] In one recent study, the median treatment duration of 9 days was found to have similar odds of recurrent infection or death within 30 days as those who received longer courses (median 16 days, interquartile range 14-17). 106 Achievement of clinical response and source control remain important clinical considerations to help guide duration of treatment.…”
Section: Duration Of Treatment Of Mdr-psamentioning
confidence: 98%
“…This observation becomes quite pertinent, during an era when shorter treatment courses are preferred for bacterial pneumonias [ 7 , 8 ]. In fact, recent data suggest that shorter (7–9 days) treatment duration may be adequate for the treatment of Gram-negative (and PSA) bacteremia [ 9 , 10 ]. It is notable that only a few allo-HCT recipients were included in those studies, which did not allow researchers to make any further conclusions on treatment duration in high-risk allo-HCT recipients.…”
Section: Discussionmentioning
confidence: 99%